1990
DOI: 10.1038/eye.1990.38
|View full text |Cite
|
Sign up to set email alerts
|

Functional anatomy of the choroidal circulation: Methyl methacrylate casting of human choroid

Abstract: SummaryThe functional anatomy of the normal choroidal circulation in man is described from scanning electron microscopic examination of methyl methacrylate microvascular casts. Distal and para-optic short posterior ciliary arteries supply wedge-shaped areas of choroid. Regional variations in choriocapillary morphology are well recog nised; the lobules are densely packed at the posterior pole with a high capillary to inter-capillary ratio. Choroidal capillaries are flattened providing a large surface area for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(103 citation statements)
references
References 27 publications
7
96
0
Order By: Relevance
“…The images of choriocapillaris obtained from single data sets have a "granular" appearance, only vaguely suggesting a mesh-like structure. Volume averaging yields a structure more convincingly resembling the appearance of choriocapillaris as imaged in histology samples [3]. A comparison between the three methods also shows differences in the influence of the retinal blood flow on the choriocapillaris imaging.…”
Section: Comparison Of Octa Imaging Of the Choroidmentioning
confidence: 80%
See 1 more Smart Citation
“…The images of choriocapillaris obtained from single data sets have a "granular" appearance, only vaguely suggesting a mesh-like structure. Volume averaging yields a structure more convincingly resembling the appearance of choriocapillaris as imaged in histology samples [3]. A comparison between the three methods also shows differences in the influence of the retinal blood flow on the choriocapillaris imaging.…”
Section: Comparison Of Octa Imaging Of the Choroidmentioning
confidence: 80%
“…Choriocapillaris is a meshwork of densely packed, interconnected vessels forming characteristic mesh-like structures. It is organized in a lobular structure [3]. Blood with nutrients is delivered by arterioles located in the centers of the lobules.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical studies of human choroidal circulation have reported that structural patterns and sizes of CC have regional variations over the retina (14,15). To demonstrate in vivo CC images at different retinal locations, we acquired pvOCT over peripheral retina (6°nasal and 12°inferior retina eccentricities) in the left eye (visual acuity: 20/60) of a 61-y-old female with geographic atrophy in the fovea.…”
Section: Resultsmentioning
confidence: 99%
“…The rbPR also suppresses these projection artifacts (Fig. 12(C1)) but shows a denser and more continuous mesh-like vascular network with small black pores where blood flow is absent, which better reflects the known scanning electron microscopy description of the vasculature [20]. [20].…”
Section: Preservation Of Choriocapillarismentioning
confidence: 69%